2016
DOI: 10.3329/ajmbr.v2i2.29009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead acetate alone and in combination with whole milk (Star ship®) on body growth and liver functions in an experimentally induced lead toxicity in rat

Abstract: The Effect of lead acetate alone and in combination with whole milk on body weight gain and some biochemical parameters were carried out on a total of 15 (15 days old) male weaning Long- Evans strain rats. The rats were randomly divided into three equal groups, each consisting of five rats. Rats of group A were kept as control (without giving any treatment), group B received lead acetate alone @ 6mg/ml drinking water and group C received lead acetate @ 6mg/ml plus whole milk (Star ship®) 150 mg/ml drinking wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These results are consistent with Elgawish and Abdelrazek (2014), who reported a significant reduction in testicular weight in lead‐treated rats. Gani et al., (2016) reported a significant reduction in rats’ body weights after treatment with lead acetate. This was explained by the interruption of absorption and metabolism of food and nutrients essential for health.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with Elgawish and Abdelrazek (2014), who reported a significant reduction in testicular weight in lead‐treated rats. Gani et al., (2016) reported a significant reduction in rats’ body weights after treatment with lead acetate. This was explained by the interruption of absorption and metabolism of food and nutrients essential for health.…”
Section: Discussionmentioning
confidence: 99%
“…Lead is a ubiquitous environmental toxin that has been detected in almost all phases of biological systems [1]. Lead results from the burning vehicle fuel, settles into the soil, and is absorbed by the plant, so food can be the source of lead exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Wabel et al (2007), reported that when 50 mg/kg lead acetate was available to rats, the serum concentration of GGT was gradually elevated from 24 IU/L to 38.3 IU/L. Gani et al (2016) revealed the familiar research conclusion when exposed the feed of rats with lead acetate. The authors reported elevated serum values of glutamate pyruvate transaminase and recorded detrimental effects on the hepatic system.…”
Section: Discussionmentioning
confidence: 99%